Neutrum dalyviai kaip įterpiniai - Valskys, Vidas (Kalbotyra, 2000)
The article analyses the syntactic and semantic characteristics of different forms of neutrum participles which act as key elements in the components of parenthetic sentences. It is argued that some neutrum principles (žinoma, suprantama, etc.), when placed in the preposition of a sentence - initial position, may be treated both as parenthetic elements and as elements of a compound sentence.The article also discusses the types of meanings and modality characteristics of neutrum participles acting as parenthetic elements.